Pengaruh Kompetensi, Motivasi, Dan Dukungan Organisasi Terhadap Efektivitas Tenaga Kependidikan Dengan Kepuasan Kerja Sebagai Veriabel Intervening - Andre Agasi; Suhardi Suhardi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
Educational staff in elementary schools play a vital role in supporting operational success; however, they often receive less attention in management studies compared to teachers. This study aims to analyze the influence of competence, motivation, and organizational support on the effectiveness of educational staff, with job satisfaction serving as an intervening variable. Employing a quantitative approach, this study involved 153 elementary school educational staff selected via stratified random sampling. Data were collected using questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that motivation has a significant positive effect on work effectiveness. Crucially, the findings reveal that organizational support does not directly influence effectiveness but is fully mediated by job satisfaction. Conversely, competence was found to have no significant effect on effectiveness, indicating a gap between technical skills and daily administrative demands. In conclusion, psychological aspects such as satisfaction and motivation are more dominant in predicting the performance of non-teaching staff than technical capacity. This study suggests that school management should focus on creating a supportive work climate that enhances employee satisfaction to achieve effective primary education services.